Health benefits of ethnic fermented foods - Santa, Dushica; Huch, Melanie; Stoll, Dominic A.; Cunedioglu, Hülya; Priidik, Reimo; Karakaş-Budak, Barçın; Matalas, Antonia; Pennone, Vincenzo; Girija, Aiswarya; Arranz, Elena; Syrpas, Michail; Mukherjee, Arghya; et al. (Frontiers in Nutrition, 2025)
Food science and technology have evolved to enhance food availability, nutrition, safety, and marketability, addressing global challenges such as hunger and malnutrition. However, projections indicate that by 2030, over 670 million people may face hunger, emphasizing the need for innovative and sustainable solutions. Ethnic fermented foods (EFF) originate from the heritage and culture of various ethnic groups who utilize their ethnomicrobiological knowledge of fermentation with local plant- or animal-based ingredients. EFF provide a promising approach to promote a healthier, sustainable, and more inclusive global food system. They are also traditionally produced by combining local ingredients with artisanal practices. However, urbanization and changes in eating habits threaten the preservation of EFF and the associated native microorganisms that are essential for their production. This research systematically examines health-related endpoints reported in human clinical studies of EFF. While some EFF such as natto, kimchi, and tempeh, originating from Asia have gained global recognition and consumption, multiple others remain unknown and understudied. This comprehensive narrative review aims to identify the potential health benefits associated with these foods. A systematic search in PubMed, Scopus, and the Cochrane Library Central initially resulted in 3,488 entries, which were narrowed down to 125 reports fulfilling the selection criteria defined to identify human studies investigating the functionality of EFF. CADIMA software was used to manage and select references. Data synthesis focused on clinical indications, offering valuable insights into health benefits of EFF, such as gut health, immune modulation, metabolic benefit, cognitive function, cardiovascular, bone, oral, eye, skin health and antimicrobial effect. This systematic narrative review highlights the importance of EFF in improving health, emphasizing their role in sustainable food systems, and underscoring the importance of preserving traditional practices.Systematic review registrationhttps://osf.io/hnksr/.